KAJIAN TENTANG PERTAUTAN HUKUM HUMANITER INTERNASIONAL DENGAN HUKUM PENGUNGSI - Riyanto, Sigit (Jurnal Media Hukum, 2013)
International Humanitarian  Law and International Refugee Law are two branchs of law relevant to the protection of human rights in a specific context. This research aimed at evaluate the relationship of these two branchs of law. Legal materials that  thoroughly considered and analized  in this research were relevant international rules and facts embodied in international customs, general principles of law, international treaties, conventions, declarations and decisions of international organisation, recommendations, academic publications, proceedings and working papers. Based upon the analysis of the existing legal materials, eventually, it could be inferred that International Humanitarian Law has influenced  International Refugee Law both in the standard setting and in the interpretation process. The rules embodied in these two branchs of law established a continuum protection for the victims of confilct with violence. Two international humanitarian agencies; International Committee of the Red Cross and the  United Nations High Commissionner for Refugees has served as the guardians in the framework of promotion and implementation of these two branchs of law. Grave breaches of International  Humanitarian Law and acts triggered international displacement were international wrongful acts and generate state responsibility.Keywords: International Humanitarian  Law, International Refugee Law, Protection, ICRC, UNHCR.